Viral Metagenomics Reveals Diverse Viruses in the Feces Samples of Raccoon Dogs - Yang, Shixing; He, Yumin; Chen, Xu; Kalim, Ullah; Wang, Yan; Yang, Shuyu; Qi, Haifeng; Cheng, HengZheng; Lu, Xiang; Wang, Xiaochun; Shen, Quan; Zhang, Wen (Frontiers in Veterinary Science, 2021)
Raccoon dogs as an ancient species of Canidae are the host of many viruses, like rabies virus, canine distemper virus, and severe acute respiratory syndrome coronavirus and so on. With the development of raccoon dog breeding in recent years, some viruses which infected poultry or pigs were also detected from raccoon dogs. At present, the fecal virome of raccoon dogs were rarely studied. Using an unbiased viral metagenomics approach, we investigated the feces virome in raccoon dogs collected from one farm of Jilin Province, China. Many DNA or RNA viruses identified in those fecal samples were mainly from seven families of Circoviridae, Smacoviridae, Genomoviridae, Parvoviridae, Picornaviridae, Astroviridae, and Hepeviridae. This study increased our understanding of the viral composition in raccoon dogs and provide first-hand information for the monitoring, prevention and treatment of viral diseases of raccoon dogs.